2016
DOI: 10.7150/ijbs.16445
|View full text |Cite
|
Sign up to set email alerts
|

Role of Osteopontin in Liver Diseases

Abstract: Osteopontin (OPN), a multifunctional protein, is involved in numerous pathological conditions including inflammation, immunity, angiogenesis, fibrogenesis and carcinogenesis in various tissues. Extensive studies have elucidated the critical role of OPN in cell signaling such as regulation of cell proliferation, migration, inflammation, fibrosis and tumor progression. In the liver, OPN interacts with integrins, CD44, vimentin and MyD88 signaling, thereby induces infiltration, migration, invasion and metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 89 publications
1
75
1
3
Order By: Relevance
“…To further elucidate the signaling pathways responsible for OPN‐induced CCR1 expression in HCC, we treated HCC cells with several pathways inhibitors, which were reported to be activated by OPN . The results revealed that only blocking the PI3K/AKT pathways by using LY294002 could significantly inhibit the OPN‐induced CCR1 expression, while U0126 or SB203580 did not have similar effects (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…To further elucidate the signaling pathways responsible for OPN‐induced CCR1 expression in HCC, we treated HCC cells with several pathways inhibitors, which were reported to be activated by OPN . The results revealed that only blocking the PI3K/AKT pathways by using LY294002 could significantly inhibit the OPN‐induced CCR1 expression, while U0126 or SB203580 did not have similar effects (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…Osteopontin, a multifunctional secreted phosphoprotein, induces collagen I expression in HSC by affecting biliary epithelial cells and promoting ductular reaction [86, 87]. Platelets are a source of pro-fibrogenic cytokines and growth factors such as PDGF, TGFβ, and EGF, and they can also suppress collagen expression via HGF-Met signaling pathway [7, 88].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…Cholangiocytes express and secrete osteopontin (OPN), a multifunctional glycophosphoprotein that can bind to integrin receptors expressed on inflammatory cells and function as a chemoattractant to neutrophils, macrophages and natural killer T cells in the liver (46, 47). Both the expression of osteopontin in biliary epithelial cells and its cleaved form in bile are significantly increased after BDL in mice, presumably caused by the stress on bile epithelial cells that results from the pressure in the biliary systems after obstruction of the bile duct.…”
Section: The Response Of Cholangiocytes To Cholestasismentioning
confidence: 99%